In Vitro Shoot Proliferation and Plant Regeneration of Phyllanthus fraternus Webster (B. Bhuiamla), a Seasonal Medicinal Herb (Bangladesh Journal of Scientific and Industrial Research, 2011)
An efficient system was developed for shoot proliferation and large scale plant regeneration of a seasonal multipotent medicinal herb, Phyllanthus fraternus Webster through in vitro culture. Shoot tips and nodal explants of young sprouts from selected plants were used as explants. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP + 0.1 mg/l GA3, in which 88% of nodal explants responded to produce maximum number (16.8 ± 0.95) of shoots per culture. In vitro raised shoots rooted on half strength MS medium with 0.5 mg/l IBA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 82%. Key words: Phyllanthus fraternus; Medicinal plant; Shoot proliferation; Regeneration; Acclimatization DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8187 Bangladesh J. Sci. Ind. Res. 46(2), 205-210, 2011